TINGKAT DEPRESI MAHASISWA DITINJAU DARI INTENSITAS PENGGUNAAN MEDIA SOSIAL - Felix Trisuko Nugroho; Alviano Karindra Syaputra, Valentinus Tourista (ADISAM PUBLISHER, 2025)
The purpose of this study was to determine the level of student depression in terms of the intensity of social media use, and to determine the relationship between the intensity of social media use and the level of depression in students. This research uses correlational research, ex post facto type. The research subjects were 250 students of the Faculty of Business, Widya Mandala Catholic University Surabaya who were determined through accidental sampling technique. The data collection technique used was a scale questionnaire consisting of measuring instruments for the intensity of social media use and the Beck Depression Inventory (BDI-II). The distribution of the research questionnaire was carried out within 2 months to get optimal results. The results showed that students had a moderate level of depression and intensity of social media use. This is evidenced in the correlation coefficient obtained 0.147 with a probability of 0.02 (p <0.05) and a coefficient of determination of (R²) 2.2%. The results showed that there is a positive relationship between the intensity of social media use and the level of depression. Thus the higher the intensity of use, the more it affects the level of depression in students